Diagnostic utility of linked color imaging in the evaluation of colonic mucosal inflammation in ulcerative colitis: a pilot study - Kanmura, Shuji; Hamamoto, Hitomi; Tanaka, Akihito; Arima, Shiho; Sasaki, Fumisato; Tanoue, Shiroh; Nasu, Yuichiro; Hashimoto, Shinichi; Higashi, Michiyo; Ido, Akio (Endoscopy International Open, 2019)
Background and aims Recent studies recommend histological mucosal healing of intestinal tissue as a treatment goal in ulcerative colitis (UC). Linked-color imaging (LCI) is a new endoscopy system that enhances the color differences of the gastrointestinal mucosa. We investigated the efficacy of LCI in the evaluation of intestinal activity, including the histological activity in UC.Method A total of 21 UC patients who were evaluated by the LASEREO system (FUJIFILM Co., Tokyo, Japan) were enrolled from August to December in 2016. All of the target points were observed by conventional white-light imaging (WLI) and LCI and biopsied from the region of interest in each view. We quantified the color tones of 73 biopsied points on WLI and LCI using the L*a*b* color value (WLI-L, WLI-a, WLI-b, and LCI-L, LCI-a, LCI-b). We then investigated the relationships among the L*a*b* color values, endoscopic findings, and histological healing.Results The average LCI-a and LCI-b values of patients with high mucosal activity disease were significantly higher than in those with mucosal healing (P < 0.01), and only LCI-a was significantly correlated with the score for histological healing. With regard to the other color values (LCI-L and all WLI values), there were no statistically significant differences in terms of average color value and correlation between patients with high mucosal activity and those with mucosal healing. In addition, the difference in the average color values with LCI and WLI was 7.1 and 3.1, respectively.Conclusion LCI is more useful than WLI for the visualization and evaluation of mucosal inflammation in UC.